The Sociological and Economic Approaches to Labor Market Analysis: A Social Structural View (translated by Maria Dobryakova) - Granovetter, Mark (Journal of Economic Sociology, 2011)
This paper presents a review of the sociological and economic approaches to labor markets in order to demonstrate their advantages and disadvantages. Comparing different views, the author proposes to construct better models of labor market which result from a merger of economists’ sophistication about instrumental behavior and sociologists’ expertise on social structure and relations, and complex mixture of motives. The author’s methodological searching is illustrated with such themes as labor mobility, implicit contracts and efficiency wages, promotion within internal labor markets.